Is micronucleus assay in oral exfoliated cells a useful biomarker for biomonitoring populations exposed to pesticides? A systematic review with meta-analysis - Malacarne, Ingra Tais (2022)
The systematic review (SR) with meta-analysis aimed to infer if micronucleus assay using oral mucosal cells a useful biomarker for biomonitoring populations continuously exposed to pesticides (EP). The SR has been made in accordance with the PRISMA-P guidelines. The PICOS strategy has focused to answer the following question: “Does exposure to pesticides cause genetic damage in oral cells?” The literature search was made in the following scientific databases: Web of Science, PubMed/Medline, and Scopus. The approach was defined as follows: standardized mean difference (SMD) and 95% confidence intervals (CI). The quality assessment of manuscripts was obtained by the EPHPP (Effective Public Health Practice Project). The GRADE tool was chosen for assessing the quality of evidence. A total of 108 articles were selected in this setting. After screening abstracts and titles, 23 manuscripts were evaluated for eligibility. After reviewing the studies, two were considered weak and 22 were classified as moderate or strong. The meta-analysis data pointed out statistically significant differences in volunteers exposed to EP (SMD = 1.23, 95% CI, 0.69 to 1.77, p < 0.001), with a Tau2 = 1.44; Chi2 = 566.38, and p < 0.001, so that the selected manuscripts were considered heterogeneous and the I2 of 97% indicated high heterogeneity. Taken together, this review was able to validate the micronucleus assay in oral exfoliated cells as a useful biomarker in individuals continuously exposed to EP because the studies categorized as moderate and strong have demonstrated positive response related to mutagenesis.